Cover Image: Volume 2 Issue 1. Issue 1 (9th February 2023) - Strehmel, Veronika; Strehmel, Bernd
Abstract : The cover picture shows colored sprites flying out of sunflowers and weaving together with colored birds a polymer network during excitation with light using the three dimethacrylate isomers and two methacrylates comprising an aromatic structure. A water droplet depositing near the center of the polymer network images contact angle measurements related to surface polarity. See the accompanying Perspective: https://doi.org/10.1002/appl.202300004